Immunization of pregnant women against pertussis: The effect of timing on antibody avidity. Issue 16 (15th April 2015) - Abu Raya, Bahaa; Bamberger, Ellen; Almog, Meital; Peri, Regina; Srugo, Isaac; Kessel, Aharon
Highlights: Gestational Tdap immunization increases the avidity of newborns PT IgG. Timing of gestational Tdap immunization affects the newborns avidity of PT IgG. PT IgG avidity increases as a function of time between Tdap boosting and delivery. Tdap immunization at 27–30 +6 weeks provides the newborns highest avidity of PT IgG. Abstract: Background: The Centers for Disease Control and Prevention recommend tetanus–diphteria–acellular pertussis (Tdap) immunization during pregnancy, preferably at 27–36 weeks gestation. Aims: First, to assess the relative avidity index (RAI) of umbilical cord immunoglobulin G (IgG) to pertussis toxin (PT) for newborns of women immunized with Tdap during late pregnancy as compared to unimmunized women. Second, to assess whether there is a preferential period of gestational Tdap immunization that provides the highest RAI of umbilical cord IgG to PT. Methods: RAI of IgG to PT was assessed via an adapted ELISA using NH4 SCN as a dissociating agent. Results: We found that newborns of women immunized with Tdap during late pregnancy ( n  = 52) had higher mean RAI of umbilical cord IgG to PT than those of unimmunized women ( n  = 8), 73.77% ± 12.08 (95% CI, 70.41–77.13) vs. 50.23% ± 21.32 (95% CI, 32.41–68.06), p  < 0.001. Further, the RAI of umbilical cord IgG to PT was significantly higher in newborns of women immunized at 27–30 +6 weeks gestation ( n  = 20) when compared with newborns of women immunized at 31–36 weeks ( n  = 22) and >36 weeks ( n  = 7), 79.53% ± 5.61 (95% CI, 76.91–82.16) vs. 71.56% ± 12.58 (95% CI, 65.98–77.14) vs. 63.93% ± 17.98 (95% CI, 47.31–80.56), p  < 0.03. Conclusion: Gestational Tdap immunization between 27 and 30 +6 weeks resulted in the highest avidity of IgG to PT conveyed at delivery as compared with immunization beyond 31 weeks gestation. Future studies should be conducted to confirm our findings to optimize pertussis-controlling strategies.